The Application of Local Wisdom in Learning: Teaching Descriptive by USing Mosaics Creative Game - Handayani, Ni Ketut Utami; Astuti, Puji (Lingua Scientia, 2011)
This research is aimed at improving the seventh graders’ achievement of SMP N 2 Kubu in descriptive writing in the academic year 2010/2011 through the application of The Palm-Mosaics Creative Game. The subjects of the research were the seventh grade students of SMP N 2 Kubu especially class VIIE, on their even semester in the academic year of 2010/2011. The total numbers of the subjects were 20 males and 20 females. This is an action based research, which was conducted in two cycles. Each cycle consisted of three sessions. Altogether, there were four steps in every cycle, namely: planning, action, observation, and reflection.